Studies of heavy metal contents and microbial composition of rhizosphere of Panicum maximum within and around auto mechanic workshop in Benin City - O Osazuwa; I Beckley; UC Osayamen (Journal of Applied Sciences and Environmental Management)
This study investigated the heavy metal content and microbial composition of rhizosphere of Panicum maximum obtained from some auto mechanic workshops in Benin City, Nigeria. The grass was uprooted and soil sample was taken from its rhizosphere. The sample were labeled appropriately and immediately  transported into a polythene bag covered with aluminium foil papers. It was then taken to the laboratory for heavy metals and microbial assay. The results showed that average plant density of Panicum maximum per 100m2 of sampled subplots in the mechanic workshops was 8.50 in Ikpoba-Okha and 9.00 in Oredo, compared to 27.50 in the control. Fe content of rhizospheric soil in Ikpoba-Okha was 1527.6 mg/kg and 1653.1 mg/kg in Egor, compared to 1002.2 mg/kg in the control. Mean heavy  metal content of rhizospheric soils was 11.71 mg/kg of Mn, 0.031 mg/kg of Pb, and 9.98 mg/kg of Cr. Total hydrocarbon content ranged from 1445.0 – 2314.2 mg/kg in the oil-polluted soils, compared to 851.5 mg/kg in the control soil. Total bacterial count of the rhizospheric soils collected from Ikpoba-Okha sampling site was 5.40 x 106 cfu/g; 5.30 x 106 cfu/g in Ovia NE, and 4.90 x 106 cfu/g in Egor, compared to 0.39 x 106 cfu/g in the control. Comparatively, bacterial counts  outnumbered fungal counts. Percentage hydrocarbon degrading fungi was 133.3% in samples collected from Oredo, compared to 31.82 in the control. The most prevalent fungal species was Aspergillus niger, whereas Micrococcus varians was the most prevalent bacterial species.